2006
DOI: 10.1002/lsm.20294
|View full text |Cite
|
Sign up to set email alerts
|

Complications following pulsed dye laser treatment of superficial hemangiomas

Abstract: Background and ObjectivePulsed dye laser (PDL) has been reported to be safe and effective in the management of superficial hemangiomas of infancy. We report 12 patients with hemangiomas with complications following PDL.Study Design/Materials and MethodsRecords of patients with hemangiomas and a known adverse outcome following PDL were reviewed.ResultsAll were treated early (age range: 5 days to 4 months), and all hemangiomas were facial with a superficial component. Eleven were treated with a 585 nm wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 36 publications
3
38
0
1
Order By: Relevance
“…This result showed that low level laser can interact with inflammatory mediators produced in different sites into respiratory system, but it does not mean that this anti-inflammatory action of laser therapy is the better effect, because is possible that the anti-inflammatory effect would be more pronounced if laser was irradiated around a more vascular part of the lung. On the contrary, the local treatment with laser seems to be an advantage because it attains only to airway and lung; thus, a possible toxic effect of LLLT can be better controlled and even avoided [35][36][37][38]. Our results reinforce the proposal of a local treatment of lung inflammation induced by LPS.…”
Section: Discussionsupporting
confidence: 84%
“…This result showed that low level laser can interact with inflammatory mediators produced in different sites into respiratory system, but it does not mean that this anti-inflammatory action of laser therapy is the better effect, because is possible that the anti-inflammatory effect would be more pronounced if laser was irradiated around a more vascular part of the lung. On the contrary, the local treatment with laser seems to be an advantage because it attains only to airway and lung; thus, a possible toxic effect of LLLT can be better controlled and even avoided [35][36][37][38]. Our results reinforce the proposal of a local treatment of lung inflammation induced by LPS.…”
Section: Discussionsupporting
confidence: 84%
“…[71][72][73][74] PDLs are generally well tolerated-side effects of their use for treatment of IHs include temporary local swelling, hyper-or hypopigmentation, and rarely pain, scarring, ulceration, or hemorrhage. 75 The PDL has been used and studied for more than 30 years as an option for treatment of IHs, and, as a result, there is substantial level III-V evidence in the form of various case reports, retrospective reviews, and small, nonrandomized prospective studies supporting its efficacy in the literature. [76][77][78][79][80][81][82][83] In 2002, the first level III evidence comparing PDL therapy to observation in the treatment of IHs was performed by Batta and colleagues 84 and raised significant doubt surrounding its efficacy.…”
Section: Pulsed Dye Laser Therapymentioning
confidence: 99%
“…A complicating factor in the interpretation of the current evidence for PDL treatment of IHs is that the studies that do show similar outcomes often use discrepant laser settings and therapy regimens, making them difficult to compare. 75 Furthermore, many of the lasers have experienced drastic changes over time based on technological advances, and, therefore, older studies using older technology may no longer be clinically relevant. More recent studies, using cooling technologies and larger spot sizes, are showing promise in the management of superficial hemangiomas.…”
Section: Pulsed Dye Laser Therapymentioning
confidence: 99%
“…The treated areas can be smeared with panthenol ointment afterwards. The patients are followed up at 2 to 4 weeks interval, and a repeated treatment may be needed after the first session, often at a 4-week interval [17] . FPDL is the first choice for laser treatment of haemangioma with good efficacy and fewer side effects.…”
Section: Treatmentmentioning
confidence: 99%